EVALUASI PENERAPAN DANA KAS KECIL PADA PT. PUTRA KARANGETANG - Wongkar, Mega Eliza; Nangoi, Grace B.; Tangkuman, Steven J. (Universitas Sam Ratulangi, 2017)
Petty cash is a cash amount owned by the company and is held or managed by a cashier whose function is to pay or finance expenses that are relatively small and tend to be routine and are immediate. The object of this research is PT. Putra Karangetang. The purpose of this research is to study how the application of accounting petty cash at the company. A data analysis method used in this research is descriptive method, which is carried out by means of collecting data related to problems encountered and serves the description of how to systematically and accurately about the facts, the nature of the relationships between phenomena investigated in a company. The results showed that the method used in the completion of petty cash fund by PT. Putra Karangetang is the fluctuation fund method, where in this method the balance of the petty cash account is not fixed (fluctuate), the number of refund is not in accordance with the expenditures of petty cash.Keywords : Accounting, Petty cash fund